The Improvement of Science Media Project Based on Scrapbook to Improve Teaching Material Design Skills of Prospective Primary Teacher Students - Novi Sari Liani; Rahmi Rahmi; Cut Roswita; Bulan Nuri (Al Hikmah: Journal of Education, 2023)
The aims of this research were to develop a scrapbook-based science media project to improve the design skills of prospective elementary school teachers. This research used quantitative research with the Research and Development (R&D) research method . With the ADDIE development model, this research used analysis, design, development, implementation and evaluation. The results of this research based on media experts clearly showed that in the media aspect, the technical quality of the scrapbook and the size of the media have a presentation value of 82.26%, 89.05%, 91.92%, so it is concluded that the results is very good. A linguist's analysis clearly showed that in terms of language clarity, suitability for student development, the size of conformity to language rules with presentation scores was 85.46%, 89.75%, 92.32% , so it was concluded to be very good . The results of the material expert analysis clearly showed that in terms of material coverage, material accuracy, up-to-dateness and stimulating desire, media presentation with presentation values was 87.56%, 89.84%, 93.12%, 90.44%, 91.61%, so it can be concluded that the results is very good. A feasibility analysis clearly showed that in the aspects of coverage of language rules, presentation of material, and coverage of conformity with presentation scores of 90.08%, 91.45%, 90.11%, it is concluded that it is very feasible. The results of the gain normality test analysis were 0.81, so it can be concluded that there has been an increase in the design skills of prospective elementary school teacher students in the high category. This was caused by scrapbook- based science media products using decorations in the form of pictures, photos and important notes that were interesting to students so that the students concentrate more on learning. The scrapbook-based science media project can improve science learning literacy.